Trend Dakwah Muballigh Milenial Analisis Terhadap Dakwah Kaum Muda di Media Sosial - Firdausi Nuzula; nawawi Hakim; lalu wahyu putra utama (Institut Agama Islam (IAI) Nurul Hakim, 2023)
Dakwah can simply be interpreted as calling for good and forbidding evil. When a Muslim obeys the call to follow the call for goodness, it is in line with the awareness to leave what is prohibited by religion. In its development, da'wah methods continue to evolve along with the dynamics of human development and innovation. Among the radical developments currently being faced by humanity are the flow of information and technological developments. This development opened up a new way of conveying the values of kindness to others. This study aims to analyze the da'wah methods used by preachers who are loved by millennials by analyzing the message of the method and content of da'wah from Hanan Attaki and Dennis Lim. The results of this study are the increasing interest of millennial youth groups in these two preachers due to several factors including the use of attribution where the preacher uses a da'wah approach in a style that is being loved by millennial youth. Besides that, substantively there is growing awareness in studying religion among millennial youth because of dictionary ideas that can affect the psychological aspects of millennial youth groups and their ability to answer personal and social problems among millennials.